Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Keterampilan Proses Dan Penguasaan Konsep Sains Ditinjau Dari Pengetahuan Awal Peserta Didik - Muhammad Wawan Fatwa; Ahmad Harjono; Jamaluddin Jamaluddin (Department of Physics Education, Universitas Mataram, 2018)
The study intended to discover : 1) the impact of Guided InquiryÃÂ Learning Model (henceforth, GILM) towards students scientificÃÂ processing skills and conceptual mastery which was reviewed from their prior knowleadgeÃÂ (high or low ), 2)ÃÂ the impact ofÃÂ students basic levelÃÂ of knowledge towardsÃÂ theirÃÂ scientific processing skills and conceptual mastery, and 3) the interaction between learning model and students prior knowledge towards their scientific processing skills and conceptual mastery. The study employed quasi experimental method with 2 x 2 factorial analyses. The study was conducted in Junior High School 2 Mataram (SMPN 2 Mataram) in academic year of 2016/2017. The sample of data collection utilized cluster random sampling technique. Both experimental and control groups were consisted of 62 students.ÃÂ Scientific processing skills and conceptual mastery observation sheets were used as research instruments. The data analyzed with Anava with SPSS version 20 for windows. The results showed that 1) there was a significant impact of GILM and conventional learning model towards studentsÃ¢â¬â¢ scientific processing skills and conceptual mastery, 2) there was no significant impact of students prior knowledge towards their scientific processing skills and conceptual mastery, 3) there was no interaction between learning models and studentsÃ¢â¬â¢ prior knowledge towards their scientific processing skills and conceptual mastery.